Functional conservation of Rel binding sites in drosophilid genomes - Copley, Richard R.; Totrov, Maxim; Linnell, Jane; Field, Simon; Ragoussis, Jiannis; Udalova, Irina A. (Genome Research, 2007)
Evolutionary constraints on gene regulatory elements are poorly understood: Little is known about how the strength of transcription factor binding correlates with DNA sequence conservation, and whether transcription factor binding sites can evolve rapidly while retaining their function. Here we use the model of the NFKB/Rel-dependent gene regulation in divergent Drosophila species to examine the hypothesis that the functional properties of authentic transcription factor binding sites are under stronger evolutionary constraints than the genomic background. Using molecular modeling we compare tertiary structures of the Drosophila Rel family proteins Dorsal, Dif, and Relish and demonstrate that their DNA-binding and protein dimerization domains undergo distinct rates of evolution. The accumulated amino acid changes, however, are unlikely to affect DNA sequence recognition and affinity. We employ our recently developed microarray-based experimental platform and principal coordinates statistical analysis to quantitatively and systematically profile DNA binding affinities of three Drosophila Rel proteins to 10,368 variants of the NFKB recognition sequences. We then correlate the evolutionary divergence of gene regulatory regions with differences in DNA binding affinities. Genome-wide analyses reveal a significant increase in the number of conserved Rel binding sites in promoters of developmental and immune genes. Significantly, the affinity of Rel proteins to these sites was higher than to less conserved sites and was maintained by the conservation of the DNA binding site sequence (static conservation) or in some cases despite significantly diverged sequences (dynamic conservation). We discuss how two types of conservation may contribute to the stabilization and optimization of a functional gene regulatory code in evolution.
10.1101/gr.6490707